2013
DOI: 10.1108/13685201311318511
|View full text |Cite
|
Sign up to set email alerts
|

The viability of enforcement mechanisms under money laundering and anti‐terrorism offences in Malaysia

Abstract: Purpose -The purpose of this paper is to give a better insight to the legal society, practitioners and legislators of the working mechanisms of money laundering activities, as well as the functionalities of the Anti-Money Laundering and Anti-terrorism Financing Act 2003 (AMLATFA) in Malaysia, in curbing money laundering and terrorism funding activities. At the same time, the paper provides an overview on the applicability and practicability of the enforcement mechanisms in Malaysia by exploring legislations fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Environmental ethics is a key concern for leaders in forefront. Spending adequately to right cause is an essentiality studies from the law perspectives focus more on the relevant legislations and statutes and their applicability within the specific legislative environment (Dhillon, Rusniah, & Aspalela, 2013). Studies from the accounting and finance perspective, on the other hand, cater on the awareness of money laundering risk and prevention measures (Ghani, Omar, & Yusuf, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Environmental ethics is a key concern for leaders in forefront. Spending adequately to right cause is an essentiality studies from the law perspectives focus more on the relevant legislations and statutes and their applicability within the specific legislative environment (Dhillon, Rusniah, & Aspalela, 2013). Studies from the accounting and finance perspective, on the other hand, cater on the awareness of money laundering risk and prevention measures (Ghani, Omar, & Yusuf, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The FATF 40 Recommendations urges all countries to establish mechanisms which allow financial investigators to obtain and share information among the law enforcement agencies. Also, it was further suggested that there must be mechanisms for investigators to use their powers to assist foreign financial investigations and also be allowed to establish and utilize joint investigative teams with law enforcement in other countries (Dhillon, et. al, 2013).…”
Section: 1findings On Phase One: the Peril Of Charities In Financimentioning
confidence: 99%
“…Any crime that generates significant profit through extortion, drug trafficking, arms smuggling and some white collar crime may create a "need" for money laundering (FATF, 2001). Similarly, recent writers have conceptualized money laundering either as a process (Rahman, 2013;Graycar and Grabosky, 1996;Unger, 2013). Simser (2013) suggests that money laundering is to clean 'dirty money" derived from criminal activities to disguise the origin of such money and to make them appear to have come from a legitimate source.…”
Section: What Is Money Laundering?mentioning
confidence: 99%